Puzzy Pic Assembly of rectangular jigsaw puzzle using artificial bee colony algorithm - Argallon, Meliton John P.; Ultra, John D.; Valleramos, Jan Van C. (Meliton John P. Argallon, John P. Ultra [and] Jan Van C. Valleramos, 2009)
A rectangular jigsaw puzzle has pieces which are rectangular in shape and of the same sizes. An automated jigsaw puzzle assembler was implemented and tested using the Artificial Bee Colony Algorithm with three different edge fitting function (EFF) namely, Pure Average, Moving Average and Block Average. All of them uses only the pixel value information on the border line of the pieces. Experiment results show that block average EFF is the best among the three as it can correctly find valid piece matches in both full-colored and black and white images. Moreover, results also show that Artificial Bee Colony is a feasible approach in solving the rectangular jigsaw puzzle problem.